DNA hypermethylation analysis in sputum for the diagnosis of lung cancer: training validation set approach - Hubers, A J (Br J Cancer, 2015)
BACKGROUND: Lung cancer has the highest mortality of all cancers. The aim of this study was to examine DNA hypermethylation in sputum and validate its diagnostic accuracy for lung cancer. METHODS: DNA hypermethylation of RASSF1A, APC, cytoglobin, 3OST2, PRDM14, FAM19A4 and PHACTR3 was analysed in sputum samples from symptomatic lung cancer patients and controls (learning set: 73 cases, 86 controls; validation set: 159 cases, 154 controls) by quantitative methylation-specific PCR. Three statistical models were used: (i) cutoff based on Youden's J index, (ii) cutoff based on fixed specificity per marker of 96% and (iii) risk classification of post-test probabilities. RESULTS: In the learning set, approach (i) showed that RASSF1A was best able to distinguish cases from controls (sensitivity 42.5%, specificity 96.5%). RASSF1A, 3OST2 and PRDM14 combined demonstrated a sensitivity of 82.2% with a specificity of 66.3%. Approach (ii) yielded a combination rule of RASSF1A, 3OST2 and PHACTR3 (sensitivity 67.1%, specificity 89.5%). The risk model (approach iii) distributed the cases over all risk categories. All methods displayed similar and consistent results in the validation set. CONCLUSIONS: Our findings underscore the impact of DNA methylation markers in symptomatic lung cancer diagnosis. RASSF1A is validated as diagnostic marker in lung cancer.